Correlation between brain function and ADHD symptom changes in children with ADHD following a few-foods diet: an open-label intervention trial - Hontelez, Saartje; Stobernack, Tim; Pelsser, Lidy M.; van Baarlen, Peter; Frankena, Klaas; Groefsema, Martine M.; Kleerebezem, Michiel; Rodrigues Pereira, Rob; Postma, Elbrich M.; Smeets, Paul A. M.; Stopyra, Marion A.; Zwiers, Marcel P.; et al. (Scientific reports, 2021)
Research into the effect of nutrition on attention-deficit hyperactivity disorder (ADHD) in children has shown that the few-foods diet (FFD) substantially decreases ADHD symptoms in 60% of children. However, the underlying mechanism is unknown. In this open-label nutritional intervention study we investigated whether behavioural changes after following an FFD are associated with changes in brain function during inhibitory control in 79 boys with ADHD, aged 8-10 years. Parents completed the ADHD Rating Scale before (t1) and after the FFD (t2). Functional magnetic resonance imaging (fMRI) scans were acquired during a stop-signal task at t1 and t2, and initial subject-level analyses were done blinded for ARS scores. Fifty (63%) participants were diet responders, showing a decrease of ADHD symptoms of at least 40%. Fifty-three children had fMRI scans of sufficient quality for further analysis. Region-of-interest analyses demonstrated that brain activation in regions implicated in the stop-signal task was not associated with ADHD symptom change. However, whole-brain analyses revealed a correlation between ADHD symptom decrease and increased precuneus activation (pFWE(cluster) = 0.015 for StopSuccess > Go trials and pFWE(cluster) < 0.001 for StopSuccess > StopFail trials). These results provide evidence for a neurocognitive mechanism underlying the efficacy of a few-foods diet in children with ADHD.
Gesehen am 20.01.2022